Binding of Various Thrombin Fractions to Fibrin and the Influence of AT-III on Their Adsorption - Nilsen, D W T; Brosstad, F; Kierulf, P; Godal, H C (Thrombosis and Haemostasis, 1986)
Human thrombin with high affinity for fibrin was obtained by subjecting purified thrombin to affinity chromatography on Sepharose insolubilized fibrin monomers, after addition of a radioiodinated subsample of thrombin, molar ratio 1:600. As judged by radioprofiling of the electrophoretic distribution of high-affinity thrombin on 10 per cent polyacrylamide gel containing urea/SDS, the preparation consisted of 70 per cent a-thrombin, 28 per cent β-thrombin and only 2 per cent γ-thrombin. Although a-thrombin was bound more strongly to insolubilized fibrin monomers than the other subfractions, complete separation of the individual components could not be achieved.High-affinity thrombin was employed for studies on thrombin adsorption to polymerized fibrin, assuming equal behaviour of labelled and unlabelled thrombin.o avoid passive entrapment of thrombin within the fibrin meshwork at physiological pH, ionic strength and calcium concentration, the optimal fibrinogen concentration was found to be 2.94 umol/1. During such conditions, adsorption of thrombin to polymerized fibrin did not exceed 65 per cent of added thrombin, despite an increasing availability of fibrin-related thrombin binding domains obtained by reducing the thrombin concentration.Adsorption of thrombin to polymerized fibrin increased by 25 per cent when the ionic strength was reduced to 0.05 mol/1. These findings suggest the presence of thrombin subfractions with different affinities for polymerized fibrin.Aggregates of high-affinity thrombin formed during its preparation by affinity chromatography, but were prevented by adding polyethylene glycol (m.w. 6,000, final conc. 6.6 g/1). Such aggregates were not inactivated by AT-III, but could still adsorb to polymerized fibrin.In its monomeric form fibrin-adsorbed thrombin was inactivated by AT-III and could then be extruded from the clot upon syneresis and retraction, but a small fraction remained attached to polymerized fibrin, exhibiting minor amidolytic activity.
Keywords: Thrombin; Fibrin; Antithrombin III; Clot interactions